2022
DOI: 10.11646/phytotaxa.532.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrosiphon annulatus sp. nov. (Oscillatoriales, Cyanobacteria) isolated on moist soil in Suwon, Republic of Korea

Abstract: Porphyrosiphon annulatus sp. nov. belonging to Microcoleaceae, Oscillatoriales was collected from the moist soil under the rock in the Gwanggyo Mountain of Suwon City, Gyeonggi Province, Korea and cultured. Using the raw and cultured samples of the collected strains, we observed their morphological features through LM and TEM. Furthermore, their 16S rRNA gene and 16S–23S rRNA intergenic transcribed spacer (ITS) sequences were determined to be used phylogenetic analyses. We affirmed that thick sheath of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…the sheath. However, several researchers later found that the sheath pigment was not stable, therefore, was not accepted as a distinguishable feature (Anagnostidis and Kom arek 1988;Kim et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…the sheath. However, several researchers later found that the sheath pigment was not stable, therefore, was not accepted as a distinguishable feature (Anagnostidis and Kom arek 1988;Kim et al 2022).…”
Section: Discussionmentioning
confidence: 99%